Analisis Faktor-faktor yang Mempengaruhi Sukuk Negara Ritel - Muhammad Ihsan Harahap (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2018)
This research aimed to determine the empirical evidences of factors affecting the price movements of sukuk retail. There are four independent variables: inflation, Bank Indonesia interest rate, Gross Domestic Product (GDP), and yield of sukuk retail with the price of sukuk retail as dependent variable. The data used range from February 2011 to June 2014. The results show that Bank Indonesia Interest rate and yield of sukuk retail significantly affect the price of sukuk retail. Simultaneously, all independent variables affect the price of sukuk retail.